2021
DOI: 10.3390/ma14030554
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Efficient Blue Phosphorescent Organic Light-Emitting Diodes (PHOLEDs) Enabled by Hole-Transport Material Incorporated Single Emission Layer

Abstract: Solution-processed blue phosphorescent organic light-emitting diodes (PHOLEDs) based on a single emission layer with small-molecule hole-transport materials (HTMs) are demonstrated. Various HTMs have been readily incorporated by solution-processing to enhance hole-transport properties of the polymer-based emission layer. Poly(N-vinylcarbazole) (PVK)-based blue emission layer with iridium(III) bis(4,6-(di-fluorophenyl)pyridinato-N,C2′)picolinate (FIrpic) triplet emitter blended with solution-processed 1,1-bis[(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…So far, much attention has been focused on the development of emission layer (EML) materials to achieve highly efficient and operationally stable OLEDs. Moreover, efforts have been directed also toward developing HTMs to advance overall device efficiencies. In particular, high triplet HTMs play an important role in obtaining high device performance by blocking triplet excitons and reinforcing recombination in the emission layer. It is well-known that only a few HTMs are reported with high E T suitable for confining triplet emitters. ,, To achieve high triplet energy, the design process utilizes the concept of molecules with twisted geometry which might affect the carrier mobility. , As a solution, we find that the high triplet energy materials could be obtained with the inclusion of a weak electron-deficient core into the molecular structure. …”
Section: Introductionmentioning
confidence: 99%
“…So far, much attention has been focused on the development of emission layer (EML) materials to achieve highly efficient and operationally stable OLEDs. Moreover, efforts have been directed also toward developing HTMs to advance overall device efficiencies. In particular, high triplet HTMs play an important role in obtaining high device performance by blocking triplet excitons and reinforcing recombination in the emission layer. It is well-known that only a few HTMs are reported with high E T suitable for confining triplet emitters. ,, To achieve high triplet energy, the design process utilizes the concept of molecules with twisted geometry which might affect the carrier mobility. , As a solution, we find that the high triplet energy materials could be obtained with the inclusion of a weak electron-deficient core into the molecular structure. …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the fabrication of PHOLEDs through solution-process is desirable for the near future due to its cost-effectiveness and applicability to large-area devices. [6][7][8][9][10][11] To realize high-performance solutionprocessed PHOLEDs, phosphorescent dopants of metal complexes should be carefully designed. Recently, many research groups reported efficient green emitters with electron-transporting ancillary ligands, such as phosphine oxide (P = O), 1,3,4-oxadiazole (OXD), triazole, and N-heterocyclic derivatives because the electron transport property of triplet emitters is a key in improving the performance of PHOLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the fabrication of PHOLEDs through solution‐process is desirable for the near future due to its cost‐effectiveness and applicability to large‐area devices. [ 6–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Since the first discovery of organic electroluminescent compounds, huge attention has been devoted to the creation of new materials and optimized multilayer device architectures for viable and practical organic light emitting diodes (OLEDs), which would demonstrate low-driving voltage, high brightness, full-color emission, a long lifetime, and the easy formation of flexible thin-film devices. The commercial benefit of OLED devices is seen in the emergence of digital cameras, mobile cell phones as well as display technologies; however, there is still a strong demand to considerably improve the performance and lifetime of the devices for lighting technologies [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%